CARDIOVASCULAR COMPLICATIONS IN DIALYSIS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
An increasing number of patients require renal replacement therapy through dialysis and renal transplantation. Chronic kidney disease (CKD) affects a large percentage of the world's population and has evolved into a major public health concern. Patients in advanced stages of CKD have varying degrees of cardiovascular damage. Comorbidities of these patients, include, on the one hand, hypertension, hyperlipidemia, hyperglycemia, hyperuricemia and, on the other hand, the presence of mineral-bone disorders associated with CKD and chronic inflammation, which contribute to cardiovascular involvement. Acute complications occur quite frequently during dialysis. Among these, the most important are cardiovascular complications, which influence the morbidity and mortality rates of this group of patients. Chronic hemodialysis patients manifest acute cardiovascular complications such as intradialytic hypotension, intradialytic hypertension, arrhythmias, acute coronary syndromes and sudden death.
Keywords: Chronic kidney disease, hemodialysis, intradialytic hypotension, high blood pressure, arrhythmia, unstable angina, acute coronary syndrome, sudden death